Derivation and validation of a sensitive IMA cutpoint to predict cardiac events in patients with chest pain. Issue 11 (22nd October 2009) - Manini, A F; Ilgen, J; Noble, V E; Bamberg, F; Koenig, W; Bohan, J S; Hoffmann, U
Abstract : Objectives: In patients with acute chest pain, we derived a cutpoint for ischaemia-modified albumin (IMA) and prospectively validated this cutpoint to predict 30-day major adverse cardiac events (MACEs). Methods: We prospectively recruited a derivation cohort (18-month period) to establish a serum IMA cutpoint targeting 80% sensitivity. This was followed by a prospective validation cohort study of emergency department patients with acute chest pain at two university hospitals over a 3-month period. A MACE was defined as myocardial infarction, revascularisation or death at 30-day follow-up. Results: In the derivation cohort of 151 patients, the IMA cutpoint that achieved 80% sensitivity for MACEs was 75 KU/litre. The sensitivity was prospectively validated in 171 patients consecutively enrolled, of whom 106 underwent multiple-biomarker analysis (19.8% MACE rate, 81% sensitivity of IMA). Furthermore, IMA by itself (81%, p<0.01) and in combination with initial highly sensitive cardiac troponin T (hsTnT) (90%, p<0.001) had significantly higher sensitivity than initial hsTnT (29%) for prediction of MACEs. Conclusions: We prospectively validated the sensitive IMA cutpoint of 75 KU/litre with 80% sensitivity for MACEs in patients with acute chest pain. Our data suggest that IMA alone and in combination with initial hsTnT are more sensitive than the initial hsTnT for MACEs.